OS1.5 Detection of glioma and prognostic subtypes by non-invasive circulating cell-free DNA methylation markers. (6th September 2019) - Noushmehr, H; Sabedot, T; Malta, T; Nelson, K; Snyder, J; Wells, M; deCarvalho, A; Mukherjee, A; Chitale, D; Mosella, M; Asmaro, K; Robin, A; et al.
Abstract: BACKGROUND: Genome-wide DNA methylation profiling has shown that epigenetic abnormalities are biologically important in glioma and can be used to classify these tumors into distinct prognostic groups. Thus far, DNA profiling has required surgically resected glioma tissue; however, gliomas release tumoral material into biofluids providing an opportunity for a minimally invasive testing. While prior studies have shown that molecular markers can be detected in liquid biopsy (LB), there has been low sensitivity for tumor-specific markers. We hypothesize that the low sensitivity is due to the targeted assay methods. METHODS: Genome-wide CpG methylation levels in DNA of tumor tissue and cell-free DNA serum of glioma patients. RESULTS: We defined glioma-specific and IDH-specific epigenetic LB (eLB) signatures (Glioma-eLB and IDH-eLB, respectively) from serum cell-free DNA from patients diagnosed with glioma (N=15 IDH mutant and N=7 IDH wildtype) and with epilepsy (N=3). The epigenetic profiles of the matched tissue demonstrate that these eLB signatures reflected the signature of the tumor. Through cross-validation we show that Glioma-eLB can accurately predict a patient's glioma from those with other neoplasias (N=6 Colon; N=14 Pituitary; N=3 Breast; N=4 Lung), non-neoplastic immunological conditions (N=22 sepsis; N=9 pancreatic islet transplantation), and from healthy individuals (sensitivity: 98%; specificity: 99%). Finally, IDH-eLB includes promoter methylated markers associated with genes known to be involved in glioma tumorigenesis (PVT1 and CXCR6). CONCLUSIONS: The application of the non-invasive eLB signature discovered in this study has the potential to complement the standard of care for patients harboring glioma. This project is supported by the Henry Ford Health System, Department of Neurosurgery and the Hermelin Brain Tumor Center Foundation (A30935), United States National Institutes of Health (R01CA222146), and United States Department of Defense (CA170278)